Perancangan Taman Kedondong sebagai Zona Aktivitas Gratis Inklusif Pendukung Interaksi Sosial Masyarakat - Arsyanda Zahra Ravanella Andiono; Wakhidah Kurniawati; Johanes Adhi Nugroho (Jurnal Riptek, 2026)
The quality of life in a city can be reflected through the availability of public spaces that facilitate both collective and individual activities. In densely populated urban areas such as Semarang, the existence of inclusive and functional parks is essential to enhance social interaction, physical health, and economic activities. To address this need, the Semarang City Government initiated the Free Activity Zone program, which provides cost-free public spaces in line with the city’s vision, mission, and development priorities. Kedondong Park, located in Lamper Tengah Subdistrict, South Semarang District, was chosen as the design site due to its dense population and limited green open space. This research aims to develop Kedondong Park into an inclusive public space that accommodates social interaction, recreation, sports, and community activities. Data collection methods include literature review, field observation, interviews, and questionnaires. The analyses applied consist of SWOT, potential–problem mapping, activity, site, and zoning, which were synthesized into the LIFE design concept: Local Economic Activation, Inclusive Social Interaction, Free Public Access, and Eco-Friendly. The design outcome is a three-dimensional proposal for Kedondong Park, emphasizing improved functionality, comfort, and quality of public space through activity zoning, supporting facilities, and strengthened elements that promote creativity, social interaction, and inclusive community engagement.